Acute effects of exercise and calorie restriction on triglyceride metabolism in women - Bellou, Elena (2013)
The mechanisms by which exercise reduces fasting plasma triglyceride (TG) concentrations in women and the effect of negative energy balance independent of muscular contraction are not known. PURPOSE: The aim of this study was to evaluate the effects of equivalent energy deficits induced by exercise or calorie restriction on basal very low-density lipoprotein (VLDL) TG metabolism in women. METHODS: Eleven healthy women (age: 23.5±2.7 years, BMI: 21.6±1.4 kg/m(2)) underwent a stable isotopically labeled tracer infusion study to determine basal VLDL-TG kinetics after performing, in random order, three experimental trials on the previous day: i) a single exercise bout (brisk walking at 60% of peak oxygen consumption for 123±18 min, with a net energy expenditure of 2.06±0.39 MJ (~500 kcal)), ii) dietary energy restriction of 2.10±0.41 MJ, and iii) a control day of isocaloric feeding and rest (zero energy balance). RESULTS: Fasting plasma VLDL-TG concentration was ~30% lower after the exercise trial compared to the control trial (P<0.001), whereas no significant change was detected after the calorie restriction trial (P=0.297 vs control). Relative to the control condition, exercise increased the plasma clearance rate of VLDL-TG by 22% (P=0.001) and reduced hepatic VLDL-TG secretion rate by ~17% (P=0.042), whereas hypocaloric diet had no effect on VLDL-TG kinetics (P>0.2). CONCLUSION: (i) Exercise-induced hypotriglyceridemia in women manifests through a different mechanism (increased clearance and decreased secretion of VLDL-TG) than that previously described in men (increased clearance of VLDL-TG only), and (ii) exercise affects TG homeostasis by eliciting changes in VLDL-TG kinetics that cannot be reproduced by an equivalent diet-induced energy deficit, indicating that these changes are independent of the exercise-induced negative energy balance but instead are specific to muscular contraction.